International experience of protecting persons in the field of public administration: what relevance of application under Ukrainian law? - Serohin, V. O.; Серьогін, В. О.; ORCID: http://orcid.org/0000-0002-1973-9310; Melikhova, Yu. A.; Voronov, M. M.; Romanenko, M. V.; Романенко, М. В.; ORCID: http://orcid.org/0000-0002-3469-2119 (Justicia. – 2021. – Vol. 26, № 40 (Julio-Diciembre). – P. 3-10, 2021)
Метою даної статті є дослідження міжнародного досвіду захисту особи у сфері державного управління та визначення можливостей його застосування в Україні. Для вищезазначеного ми використали аналітичний метод та аналіз документації, щоб відстежити теоретичні основи та зрозуміти поточний стан захисту осіб у сфері державного управління. Важливе значення та визнання на цій дослідницькій платформі набули актуальні питання, пов’язані з реалізацією законодавчих методів захисту особи у сфері державного управління. Вивчено досвід зарубіжних країн у сфері захисту особи під час її відносин з органами державної влади; визначено можливості його застосування в Україні. Підкреслено, що здатність будь-якої особи використовувати законодавчо визначені засоби правового захисту є однією з ключових ознак правової держави. Зазначається, що по-справжньому правовою і демократичною може вважатися тільки та країна, державна влада якої виконує свої безпосередні функції з державного управління без шкоди для прав, свобод і законних інтересів особи. Наведено та порівняно наукові точки зору щодо реалізації законодавчо визначених процедур захисту особистості у сфері державного управління. Зазначено, що впровадження ефективних методів і засобів захисту особи є надзвичайно важливим аспектом діяльності органів державної влади, особливо в контексті євроінтеграційного курсу України.

The purpose of this article is to study international experience of protecting persons in the field of public administration and determining the possibilities of its application in Ukraine. For the above, we used the analytical method and the documentary analysis to track theoretical background and to understand the current state of protecting persons in the field of public administration. Relevant issues related to the implementation of statutory methods of protecting persons in the field of public administration have been of great importance and recognition in this research platform. The experience of foreign countries in the field of protecting persons during their relations with public authorities has been studied; the possibilities of its application in Ukraine have been determined. It has been emphasized that the ability of any person to use the legally defined tools of legal protection is one of the key features of the rule of law state. It has been noted that only a country whose state power performs its direct functions on public administration without harming the rights, freedoms and legitimate interests of individuals, can be truly considered legal and democratic. Scientific points of view on the implementation of legally defined procedures for the protection of individuals in the field of public administration have been provided and compared. It has been noted that the introduction of effective methods and means of protection of persons is an extremely important aspect of state authority’s activity, and especially in the context of Ukraine’s European integration course.

Целью данной статьи является изучение международного опыта защиты лиц в сфере государственного управления и определение возможностей его применения в Украине.
Experiencia internacional de las personas protectoras en el campo de la administración pública: ¿qué tan relevante es la aplicación de acuerdo con la ley ucraniana?
International experience of protecting persons in the field of public administration: what relevance of application under Ukrainian law? / Vitalii Oleksandrovych Serohin, Yuliia Anatoliivna Melikhova, Mark Mykolayovych Voronov, Maryna Volodymyrivna Romanenko // Justicia. – 2021. – Vol. 26, № 40 (Julio-Diciembre). – P. 3-10. – DOI: https://doi.org/10.17081/just.26.40.4870.
Oleksandrovych Serohin, V. ., Anatoliivna Melikhova, Y., Mykolayovych Voronov, M., & Volodymyrivna Romanenko, M. (2021). Experiencia internacional de las personas protectoras en el campo de la administración pública: ¿qué tan relevante es la aplicación de acuerdo con la ley ucraniana?. Justicia, 26(40), 3–10. https://doi.org/10.17081/just.26.40.4870.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Міжнародне право .International Law. Международное право; Україна. Ukraine. Украина; international experience; protection of rights and legitimate interests; civil society; public administration; міжнародний досвід; захист прав і законних інтересів; громадянське суспільство; державне управління; международный опыт; защита прав и законных интересов; гражданское общество; государственное управление; publikatsii u WoS